Tectonically controlled initiation of contemporaneous deep‐water channel systems along a Late Cretaceous continental margin, western British Columbia, Canada. Issue 7 (16th May 2018) - Englert, Rebecca G.; Hubbard, Stephen M.; Coutts, Daniel S.; Matthews, William A.
Abstract: Submarine channel‐systems are globally prevalent on continental margins and their deposits record the transfer of significant volumes of sediment from continental catchments to deep‐water environments. These deposits contain signals of past events that can provide critical insight into the geological history of an area, including the long‐term (>1 Ma) controls on sedimentation. Well‐exposed outcrops of the Late Cretaceous Nanaimo Group, British Columbia, Canada, provide an opportunity to investigate long‐term sediment‐routing in a tectonically active setting. This study combines detrital zircon geochronology with stratigraphic analysis to establish a robust, basin‐wide palaeogeographic framework that constrains the timing and distribution of coarse‐grained sediment transport and deposition in the Nanaimo forearc basin. Three south‐west trending submarine conduits are documented along a 135 km long strike‐oriented transect, parallel to the north‐west/south‐east trending basin. Composite conduit deposits are 350 to 700 m thick, 4 to 16 km wide, and record substantial delivery of coarse‐grained detritus (up to boulder‐sized clasts) within submarine channel‐levée systems. Maximum depositional ages derived from detrital zircon datasets constrain contemporaneous sediment transfer and deposition at each conduit location, which spanned between 73·5 ± 1·3 Ma to 69·1 ± 1·1 Ma around the Campanian–Maastrichtian boundary. Submarine conduits are spaced at 40 km and 70 km, and were likely connected to fluvial drainage systems sourced in uplifted catchments. Widespread, coarse‐grained deposits suggest that surface uplift associated with concurrent regional events (such as deformation and/or magma emplacement) along the North American margin may have promoted sediment delivery to the deep‐water basin. Comparisons to modern and ancient analogues support palaeogeographic interpretations, as well as the interpretation that pervasive coarse‐grained deep‐water sediment delivery was linked to tectonic activity. The integrated stratigraphic–geochronological approach used provides unique insight into the influence of regional tectonics on continental margin physiography and the nature of deep‐water sediment dispersal.